An Analysis of Grammatical Errors in English Public Signage of TransJakarta - Sari, Margareta Anita; Rosalinah, Yanti (Universitas Ahmad Dahlan, 2025)
This study investigates grammatical errors in English public signage displayed within the TransJakarta transportation system. It aims to identify, classify, and interpret linguistic inaccuracies and explore their social implications within Jakarta’s multilingual context. Data were collected through direct field observation and documentation of bilingual signs found at bus stops and on buses. The analysis applied grammatical frameworks from Carter and McCarthy (2021) and the error typology of Ariani and Artawa (2022), while sociolinguistic interpretation was guided by Nenotek et al. (2024). To strengthen the theoretical basis, this paper also draws upon recent linguistic studies emphasizing the role of grammar awareness (Wulandari & Harida, 2021; Warregh, 2025) and technological correction models (Qin, 2022; Wang et al., 2024; Zhong & Yue, 2022). Findings reveal frequent grammatical inaccuracies, especially article omission, determiner misuse, and sentence structure omission, mainly caused by literal translation from Bahasa Indonesia. The study concludes that improving linguistic accuracy in public signage enhances clarity, supports inclusivity, and reflects Jakarta’s global image.